2019
DOI: 10.1002/adma.201901979
|View full text |Cite
|
Sign up to set email alerts
|

Graphene‐Based Fibers: Recent Advances in Preparation and Application

Abstract: investigated [17][18][19][20] for building graphene-based fibers (GBFs) over recent years. [21][22][23] These unique macroscopic 1D assemblies of microscopic 2D graphene building blocks are of lightweight, high specific surface area (SSA), and remarkable mechanical and electrical properties, thus qualifying them as ideal materials for fiber electronics. [14,[24][25][26] Currently, the well-developed wet-spinning method is widely adopted in preparing GBFs, [27,28] while newly designed spinning methods with micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 117 publications
0
69
0
1
Order By: Relevance
“…[92] Graphene is arguably the thinnest and lightest material in the world, and its tightly packed conjugated hexagonal lattice structure makes it have excellent physical and chemical properties. [93][94][95][96][97][98] For example: extremely large specific surface area, high mechanical strength, 200 times higher than steel, and a tensile modulus (stiffness) at 1 TPA (150, 000, 000 psi). It has excellent thermal conductivity and its thermal conductivity is up to 5300 W/m•K.…”
Section: Electrocatalytic Reduction Of Co 2 By Phthalocyanine/graphenmentioning
confidence: 99%
“…[92] Graphene is arguably the thinnest and lightest material in the world, and its tightly packed conjugated hexagonal lattice structure makes it have excellent physical and chemical properties. [93][94][95][96][97][98] For example: extremely large specific surface area, high mechanical strength, 200 times higher than steel, and a tensile modulus (stiffness) at 1 TPA (150, 000, 000 psi). It has excellent thermal conductivity and its thermal conductivity is up to 5300 W/m•K.…”
Section: Electrocatalytic Reduction Of Co 2 By Phthalocyanine/graphenmentioning
confidence: 99%
“…In fact, skin contact is one of the most relevant exposure routes to these materials, considering both an occupational scenario and specific ones related to skin applications of GBMs [ 8 , 9 ]. The latter consists of GBM-enriched devices used as biosensors, wearable soft bioelectronics and novel touchscreens, but can be represented also by GBM-enriched novel textiles, seat coatings and even new-generation condoms, among others [ 19 , 20 , 21 , 22 ]. In this regard, we already characterized the in vitro toxic effects induced by short (24 h) and long (72 h) exposures to GBMs on skin HaCaT keratinocytes, a spontaneously immortalized non-tumor cell line that, resembling the functional properties of undifferentiated keratinocytes, is widely used as a screening tool to assess the mechanism of cutaneous toxicity [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wideangle X-ray scattering (WAXS) technique can be informative about the structure and orientation degree along the fiber axis (Xu et al, 2012(Xu et al, , 2016Alemán et al, 2015). Small-angle X-ray scattering (SAXS) was performed by Xu et al (2012Xu et al ( , 2019 to investigate the size and shape confinements in the fiber of the carbon building blocks and optimize the fluid dynamics in the wet-spinning of the graphene fiber fabrication (2D SAXS configuration). Lamellar structural information is of particular interest when GO or liquid crystals are used in presence of nematic, lamellar and chiral compounds (Kumar et al, 2017;Clancy et al, 2018;Fang et al, 2020).…”
Section: A-few Characterization Techniquesmentioning
confidence: 99%
“…On the other hand, metals are present in nature with limited amounts and the need for an advantageous alternative solution would be of great relevance. Under these perspectives, it is important to remark that many reviews concerning the main topic of the carbon-based materials and properties are present and that a certain number of them (Chou et al, 2010;Lu et al, 2012;Cong et al, 2014;Lekawa-Raus et al, 2014b;Li and Pandey, 2015;Xu and Gao, 2015;Kou et al, 2017;Yadav et al, 2017;Xu et al, 2019;Zheng et al, 2020) should be nevertheless deemed of a great significance. Along with recent findings, Zheng et al (2020) have recently demonstrated the ultrafast electro-thermal response (5943 K s −1 ) of graphene fibers surpassing the record value of carbon nanotubes.…”
Section: Introductionmentioning
confidence: 99%